Innovative empirical model for predicting national banks' financial failure with artificial intelligence subset data analysis in the United States - Karina Kasztelnik (Open Economics, 2020)
The principal objective of this research study was to investigate the impact of the Great Economic Recession of 2008 on national banks' equity investment valuations and create an empirical model for predicting national banks' financial failure in the United States. The focal period of the study was from 2009 to 2012, and public data sources used. It is not known to what extent national banks' stock value investments are based on the return on equity. This causal-comparative study explores the degree to which national banks' value investment in terms of the price to earnings ratio impacts their return on equity and the extent to which these banks' stock value investment in terms of dividend yield impacts their return on equity. We used statistical modeling and the machine learning model to find hidden patterns in the input data. The principal finding of this research is that the median earnings per share in 2012 and the dividend yield in 2009 were significantly larger than the median return on equity in 2009 and 2012. Additionally, the dividend yield in 2012 was significantly smaller than the median return on equity in 2012. These findings can contribute to improving our understanding of how banks can predict financial failure using the new machine learning features of artificial intelligence to build an early warning system with the innovative risk measurement tool.
Keywords: M21; M41; O51; G24; N20; 330; ROE; Equity Valuations; Financial Institutions; Economic Recession; Dividend Yield; Price toEarnings; Banks